Scientology 8-80: The discovery and increase of life energy in the genus homo sppiens. - Hubbard, L. Ron (Denmark Scientology Publications Organizations., 1979)
From the Book Jacket: Scientology 8-80 reveals the first explanation of the electronics of human thought and beingness, demonstrating how physical universe laws of motion operate in any being. Here also is the milestone breakthrough of "Black and White" and "Concept Processing"--The means to overcome and eradicate facsimiles by the hundreds and thousands.
Keywords: Scientology; Natural science